ACTIVITY DAILY LIVING : STUDI PADA LANJUT USIA DI BINA KELUARGA LANSIA POSYANDU CEMPAKA KABUPATEN NGAWI - Diana Ariswanti Triningtyas; Siti Muhayati (Universitas Muhammadiyah Semarang, 2018)
Aging is a closing period in the span of human life. Living a happy and prosperous old age is a dream for all elderly people, especially the elderly at the CempakaPosyandu in Ngawi. Changes in physical conditions in the aging process that occur in various aspects of elderlylife, both personally, family and community. This research was conducted to determine the activity of daily living in the elderly in the Elderly Family Development of CempakaNgawiPosyandu, with a total of 18 research subjects.The results showed that the independence of the elderly in fulfilling the activities of daily life contributed greatly. Activities of daily life in the elderly in life in society must be able to adjust to the changes that occur. Conditions affecting this include economic, health and social conditions.Keywords: Activities of daily life, elderly